1997
DOI: 10.1029/96ja03340
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of subkilometer scale ionospheric irregularities generated by high‐power HF waves

Abstract: Abstract. Electron density irregularities in the F region excited by the European incoherent scatter (EISCAT) high-power high-frequency (HF) facility in Ramfjordmoen, Norway, have been studied in detail by observing scintillations of 250-MHz satellite signals traversing the HF beam. Spaced antenna measurements were performed to determine the temporal structure of scintillation and the drift of the irregularities. Studies of scintillation spectra indicate that even though the onset occurs nearly simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…Theory by Guzdar et al [1996] found that self-focusing favors large transverse scale sizes (>km) because diffraction effects suppress self-focusing at shorter wavelengths. Scintillation observations at EISCAT confirm this idea [Basu et al, 1997]. However, the growth time of km scale irregularities is minutes in contrast tens of seconds for 10 m scale irregularities and seconds for meter-scale irregularities [Basu et al, 1997].…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Theory by Guzdar et al [1996] found that self-focusing favors large transverse scale sizes (>km) because diffraction effects suppress self-focusing at shorter wavelengths. Scintillation observations at EISCAT confirm this idea [Basu et al, 1997]. However, the growth time of km scale irregularities is minutes in contrast tens of seconds for 10 m scale irregularities and seconds for meter-scale irregularities [Basu et al, 1997].…”
Section: Introductionsupporting
confidence: 53%
“…Scintillation observations at EISCAT confirm this idea [Basu et al, 1997]. However, the growth time of km scale irregularities is minutes in contrast tens of seconds for 10 m scale irregularities and seconds for meter-scale irregularities [Basu et al, 1997].…”
Section: Introductionsupporting
confidence: 53%
“…Djuth et al, 2005). Such structures were also obtained by different radio methods and in-situ measurements (Basu et al, 1997;Kelley et al, 1995;Frolov et al, 2001;Myasnikov et al, 2001;Djuth et al, 2006). The existence of such structures is supported by theoretical predictions (e.g.…”
Section: Introductionmentioning
confidence: 54%
“…The plasma density inside these striations is a few percent less than that of the ambient plasma. These plasma striations have a wide range of scales l Ќ across the geomagnetic field from a few decimeters 1 or less to meter scale 2,3 as obtained from radar scatter measurements, subkilometer scales as obtained from scintillation measurements of radio star and satellite signals, 4,5 up to more than a kilometer as obtained from comparing density fluctuations measured by satellite and radar plasma line fluctuations. 6 During pump beam self-focusing in high-latitude experiments, evidence of density striations with scales of a few kilometers across the geomagnetic field were observed in optical emissions during pumping in geomagnetic zenith.…”
Section: Introductionmentioning
confidence: 99%